2017
DOI: 10.1111/resp.13050
|View full text |Cite
|
Sign up to set email alerts
|

Physiological effects of titrated oxygen via nasal high‐flow cannulae in COPD exacerbations: A randomized controlled cross‐over trial

Abstract: Short-term use of NHF results in a small reduction in PtCO compared with SNP in patients with acute exacerbations of COPD, but whether this is clinically significant is uncertain.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
123
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 86 publications
(129 citation statements)
references
References 31 publications
(81 reference statements)
6
123
0
Order By: Relevance
“…A randomized cross‐over study (long‐term oxygen therapy versus HFOT at 30 L/min with room air) confirmed that HFOT reduced CO 2 rebreathing, and also showed that it increased tidal volume and improved breathing pattern with a reduction of respiratory rate without any change in minute ventilation . Similar results have been reported, even in patients with acute exacerbation of COPD …”
Section: Niv As First‐line Treatment For Acute Respiratory Acidosis Dsupporting
confidence: 69%
“…A randomized cross‐over study (long‐term oxygen therapy versus HFOT at 30 L/min with room air) confirmed that HFOT reduced CO 2 rebreathing, and also showed that it increased tidal volume and improved breathing pattern with a reduction of respiratory rate without any change in minute ventilation . Similar results have been reported, even in patients with acute exacerbation of COPD …”
Section: Niv As First‐line Treatment For Acute Respiratory Acidosis Dsupporting
confidence: 69%
“…In this issue of Respirology , Pilcher et al . published a study of NHF use in patients with an acute exacerbation of COPD (AECOPD).…”
Section: Results Of Different Studies Documented Decrease In Hypercapmentioning
confidence: 99%
“…6,7 In addition, preliminary data are available that demonstrate a potential effectiveness in decreasing hypercapnia. [6][7][8][9][10][11] In this issue of Respirology, Pilcher et al 12 published a study of NHF use in patients with an acute exacerbation of COPD (AECOPD). The investigators prospectively evaluated the influence of titrated oxygen via NHF in a single-centre randomized crossover trial versus low flow oxygen from standard nasal prongs (SNPs).…”
mentioning
confidence: 99%
“…Pilcher et al . found that O 2 delivered via high‐flow nasal cannulae in acute COPD exacerbations reduced CO 2 slightly at 30 min.…”
Section: Copdmentioning
confidence: 99%
“…Pilcher et al 34 found that O 2 delivered via high-flow nasal cannulae in acute COPD exacerbations reduced CO 2 slightly at 30 min. High-flow nasal oxygen is an emergent and potentially important treatment modality in COPD which deserves further research.…”
Section: Non-pharmacological Managementmentioning
confidence: 99%